Development and Validation of Prognostic Nomogram in Patients With WHO Grade III Meningioma: A Retrospective Cohort Study Based on SEER Database - Jia, Zetian; Yan, Yaqi; Wang, Jiuxin; Yang, He; Zhan, Haihua; Chen, Qian; He, Yawei; Hu, Yuhua (Frontiers in Oncology, 2021)
Abstract Introduction: World Health Organization (WHO) Grade III meningioma is a central nervous system tumor with a poor prognosis. In this retrospective cohort study, the authors constructed a nomogram for predicting the prognosis of WHO Grade III meningioma. Methods: The patients of this nomogram were based on the Surveillance, Epidemiology, and End Results (SEER) database between 2000 and 2018. All patients were randomly divided into a development cohort (964 patients) and a validation cohort (410 patients) in a 7:3 ratio. The least absolute shrinkage and selection operator (LASSO) regression was used to screen the predictors. The Cox hazards regression model was constructed and the prognosis was visualized by nomogram. The performance of the prognostic nomogram was determined by consistency index (C-index), clinical net benefit, and calibration. Results: Eight variables were included in the nomogram: gender, race, age at diagnosis, histology, tumor site, tumor size, laterality, and surgical method. The C-index of the training set and verification set were 0.654 and 0.628. The calibration plots showed that the nomogram was in good agreement with the actual observation. The clinical decision curve indicates that the nomogram has a good clinical net benefit in WHO Grade III meningioma. Conclusions: A prognostic nomogram of a large cohort of WHO Grade III meningioma was established and verified based on the SEER database. The nomogram we established may help clinicians provide personalized treatment services and clinical decisions for patients.